Trust management XII : 12th IFIP WG 11.11 International Conference, IFIPTM 2018, Toronto, ON, Canada, July 10-13, 2018, Proceedings /: 12th IFIP WG 11.11 International Conference, IFIPTM 2018, Toronto, ON, Canada, July 10-13, 2018, Proceedings. (2018) - Unknown
No abstract available